If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 23 = 2x + 8 Reorder the terms: 23 + -1x = 2x + 8 Reorder the terms: 23 + -1x = 8 + 2x Solving 23 + -1x = 8 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 23 + -1x + -2x = 8 + 2x + -2x Combine like terms: -1x + -2x = -3x 23 + -3x = 8 + 2x + -2x Combine like terms: 2x + -2x = 0 23 + -3x = 8 + 0 23 + -3x = 8 Add '-23' to each side of the equation. 23 + -23 + -3x = 8 + -23 Combine like terms: 23 + -23 = 0 0 + -3x = 8 + -23 -3x = 8 + -23 Combine like terms: 8 + -23 = -15 -3x = -15 Divide each side by '-3'. x = 5 Simplifying x = 5
| 3(m+3)+24=69 | | 2x+x+y=100 | | 7x(12/6-2)^2-6 | | h-27/-7=-9 | | 7x+55=3x+23 | | 9(m+1)=54 | | 3(s+22)+10=88 | | -12/r=-3 | | -c^2+c+30=0 | | -3(s+18)=-15 | | 6x+40=2x+4 | | 6(k-74)-5=83 | | 6=4-w | | x+17=5x+5 | | 6=-3(d-9) | | 2(7x+8)-4=28 | | 288=X+0.06X | | t-7/3=3 | | 4x+31=x+7 | | 12/n=3 | | 4x+11=x+1 | | 2/3x5/6x | | 8-51nx=3 | | 5x-26=x+6 | | x+(x*0.3)=5540.12 | | (x+(x*0.3))=5540.12 | | (X*.4)+X=4250 | | (2*.4)+X=4250 | | X*5+9=34 | | 9X*.40+X=4250 | | 6y=4y+24 | | 2X*.5=4250 |